Alexander Graham Bell - Pollard, Michael; Electricity & Electronics (Exley Publishing Ltd, 1991)
The story of Alexander Graham Bell is about his invention, the telephone, and its effect on people's lives. As a person who had dedicated his life to helping the deaf, Bell once heard a voice vibration coming through a piece of stretched wire. His experiments and invention of the telephone changed the way people communicate. Later Bell produced an astounding number of inventions, including the first hydrofoil, an air conditioning system, the first iron lung, and an early version of a fax machine.
Keywords: Science & Technology; Juvenile Nonfiction; Biography & Autobiography; Juvenile Nonfiction; Technology